1988
DOI: 10.1001/archotol.1988.01860220097032
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Surgical Adjuvant Trial of Interferon Alfa-n1 in Recurrent Papillomatosis

Abstract: \s=b\ Sixty-six patients with recurrent respiratory papillomatosis of juvenile onset were treated for six months with interferon alfa-n1 (Wellferon) in a randomized crossover trial. Half received interferon alfa-n1 intramuscularly at a dosage of 5 megaunits per square meter daily for 28 days and then thrice weekly for five months, followed by six months of observation. The other half were observed for six months and then treated. Operations were performed every two months to assess disease extent by a scale de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 18 publications
0
31
0
2
Order By: Relevance
“…Alpha-interferon is an immunomodulatory cytokine with antiviral and antiproliferative properties and was the first widely used adjuvant drug for treating RRP, with diverse results ranging from better prognosis to absence of response. 6,9 The evidence has failed to support its use, since the reports have mostly been based on case reports and clinical trials have shown varied results with limited follow-up. 6,9,10 The association between interferon and polyethylene glycol, which is called pegylated interferon, increases the half-life of the drug, eliminates immunogenicity and improves the pharmacokinetics of the protein, such that it can be administered once a week.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-interferon is an immunomodulatory cytokine with antiviral and antiproliferative properties and was the first widely used adjuvant drug for treating RRP, with diverse results ranging from better prognosis to absence of response. 6,9 The evidence has failed to support its use, since the reports have mostly been based on case reports and clinical trials have shown varied results with limited follow-up. 6,9,10 The association between interferon and polyethylene glycol, which is called pegylated interferon, increases the half-life of the drug, eliminates immunogenicity and improves the pharmacokinetics of the protein, such that it can be administered once a week.…”
Section: Discussionmentioning
confidence: 99%
“…In this context no significant differences in the frequency of HBsAg negativization or serum HBV DNA clearance were observed between treated and control healthy HBsAg carriers. Finally, several investigators [Real et al, 1986;Kabbash et al, 1988;Leventhal et al, 1988] found that IFN alpha treatment may lead to liver toxicity, with an ALT increase in different diseases. In this sense, it has been reported that IFN alpha may increase ALT levels in as many as 64% of patients with recurrent respiratory papillomatosis who had normal base line ALT values and were treated with a similar dose and type of IFN alpha as were used in our study, and for the same treatment period [Leventhal et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several investigators [Real et al, 1986;Kabbash et al, 1988;Leventhal et al, 1988] found that IFN alpha treatment may lead to liver toxicity, with an ALT increase in different diseases. In this sense, it has been reported that IFN alpha may increase ALT levels in as many as 64% of patients with recurrent respiratory papillomatosis who had normal base line ALT values and were treated with a similar dose and type of IFN alpha as were used in our study, and for the same treatment period [Leventhal et al, 1988]. Moreover, IFN alpha has been used to treat the AIDS-associated Karposi's sarcoma, and a direct relation between ALT increase and IFN treatment was reported in these patients [Real et al, 1986;Kabbash et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…Interferon is one of the initial adjuvant therapies introduced to treat JORRP and has been tried on a large number of patients [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Reviewmentioning
confidence: 99%
“…Prolonged treatment seems to be more favorable as it may lead to sustained response and decreased relapses. Side effects included neutropenia [9,10,13,17,18], thrombocytopenia [10], liver dysfunction [10,11,[13][14][15]17,18], nausea [11,13], anorexia [11,13,14,17,18], fatigue [10,13,16,17], vomiting [11], chills [13,18], myalgia [18], weight loss [18], malaise [10], headache [13,[16][17][18], mild to moderate alopecia [14,17], palmar erythema [15], flu-like syndrome [15], depression [16], mild lethargy [17], disorientation [18], seizure [18], febrile seizure [17], drowsiness [18], and increased bronchial secretions [18].…”
Section: Reviewmentioning
confidence: 99%